Passivity-based Proportional Integral Tuning Method for a Simple Heat Exchanger Network - Mahitthimahawong, Siwaporn; Chaiwattanapong, Nitipat; Paterson, Tony; Srinophakun, Thongchai (Agriculture and Natural Resources, 2014)
A more realistic heat exchanger model was developed by implementing a bypass control loop. Under the decentralized unconditional stability (DUS) condition, proportional integral (PI) tuning parameters were designed based on the passivity concept to maintain closed-loop stability. The controller’s performance was tested with a simple heat exchanger network (HEN) under various inlet ﬂow rates of hot stream using an Aspen Dynamics simulator. The results indicated that the proposed controller can reject the disturbance and give faster and better setpoint tracking than conventional PI controllers based on the Ziegler-Nichols method. In addition, this proposed controller could handle the entire process at the target setpoint even with sluggishness in one control loop whereas the conventional controller could not operate properly and all responses were too slow.